Jesus and the World of Grace, 1968-2016 An Idiosyncratic Theological Memoir - Portier, William L. (2016)
This article offers an impressionistic look back over the past five decades, from 1968 to 2016, in Catholic theology in the United States. At the heart of this story are Christology, the world of grace, and their relationship. This memoir unfolds in three parts: "Running on Empty, 1968-1980"; "Jesus and the World of Grace, 1980-2016"; "Can Liberal Catholics Come Back?" It identifies the most neuralgic question left to us from this period: How is Christ related to the world of grace?
Keywords: Christology; Gaudium et Spes; Vatican II; seeking God in all things; world of grace